How fruit developmental biology makes use of flow cytometry approaches. Issue 2 (22nd November 2013) - Pirrello, Julien; Bourdon, Matthieu; Cheniclet, Catherine; Bourge, Mickaël; Brown, Spencer C.; Renaudin, Jean‐Pierre; Frangne, Nathalie; Chevalier, Christian
Abstract Fleshy fruit species such as tomato are important because of their nutritional and economic value. Several stages of fruit development such as ovary formation, fruit set, and fruit maturation have already been the subject of many developmental studies. However, fruit growth per se has been much less addressed. Fruit growth like all plant organs depends upon the developmental processes of cell division and cell expansion. The activity of cell divisions sets the number of cells that will compose the fruit; the cell expansion activity then determines its final size. Among the various mechanisms that may influence the determination of cell size, endopolyploidy by the means of endoreduplication, i.e. genome amplification in the absence of mitosis, appears to be of great importance in fleshy fruits. In tomato fruit, endoreduplication is associated with DNA‐dependent cell expansion: cell size can reach spectacular levels such as hundreds of times its initial size (e.g. >0.5 mm in diameter), with as much as a 256‐fold increase in nuclear DNA content. Using tomato fruit development as a model, recent investigations combining the use of flow cytometry, cellular imaging and molecular analyses have provided new data in favor of the long‐standing karyoplasmic ratio theory, stating that cells tend to adjust their cytoplasmic volume to the nuclear DNA content. By establishing a highly structured cellular system where multiple physiological functions are integrated, endoreduplication acts as a morphogenetic factor supporting cell growth during tomato fruit development. In the context of plant breeding, deciphering the mechanisms controlling fruit growth, in particular those connecting the process of nuclear endoreduplication with modulation of gene expression, the regulation of cell size and final fruit size and composition, is necessary to understand better the establishment of fleshy fruit quality traits. © 2013 International Society for Advancement of Cytometry